Health‐related quality‐of‐life impact of pembrolizumab versus best supportive care in previously systemically treated patients with advanced hepatocellular carcinoma: KEYNOTE‐240. Issue 6 (24th November 2020) - Ryoo, Baek‐Yeol; Merle, Philippe; Kulkarni, Amit S.; Cheng, Ann‐Lii; Bouattour, Mohamed; Lim, Ho Yeong; Breder, Valeriy; Edeline, Julien; Chao, Yee; Ogasawara, Sadahisa; Yau, Thomas; Garrido, Marcelo; et al.
Abstract : Background: Health‐related quality of life (HRQoL) is an important outcome measure and prognostic indicator in hepatocellular carcinoma (HCC). KEYNOTE‐240 (NCT02702401) assessed the efficacy and safety of pembrolizumab plus best supportive care (BSC) versus placebo plus BSC in patients with HCC who previously received sorafenib. This study presents the results of a prespecified exploratory analysis of patient‐reported outcomes. Methods: Patients completed the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire (EORTC QLQ‐C30) and its HCC supplement (EORTC QLQ‐HCC18) electronically at baseline; at weeks 2, 3, 4, 6, 9, 12, and 18; and then every 9 weeks until 1 year or end of treatment, and at the 30‐day safety follow‐up visit. Results: The HRQoL population included 271 and 127 patients randomly assigned to pembrolizumab and placebo, respectively. From baseline to week 12, changes in both scores were similar between pembrolizumab and placebo; global health status/QoL scores were stable. The proportions of patients who improved, remained stable, or deteriorated across all functional domain and symptom scores were generally similar between pembrolizumab and placebo. Time to deterioration was similar between the 2 arms based on the prespecified analysis of EORTC QLQ‐HCC18 domains of abdominal swelling, fatigue, and pain. Conclusion: Pembrolizumab preserved HRQoL during treatment for advanced HCC. Combined with efficacy and safety results from KEYNOTE‐240, these findings support a positive benefit/risk profile for pembrolizumab in a second‐line treatment setting for patients with HCC who previously received sorafenib. Abstract : Pembrolizumab preserves health‐related quality of life during treatment in patients with advanced hepatocellular carcinoma (HCC) who had progression during or after or were intolerant to sorafenib. The results of this prespecified exploratory analysis combined with efficacy and safety data from KEYNOTE‐240 support a favorable risk–benefit profile for pembrolizumab in a second‐line treatment setting for patients with HCC who previously received sorafenib.